Cross-country differences in the effect of political connections on stock price informativeness - Yuanto KUSNADI, (Institutional Knowledge at Singapore Management University, 2016)
Using a sample of firms from 28 countries, we investigate the cross-country differences in the effect of political connections on the information environment. We find that politically connected firms in the emerging markets exhibit lower stock price informativeness than similar unconnected firms but we do not find this result in the developed markets. This finding is robust to controlling for earnings quality, analyst coverage, share-turnover, and insider ownership. Examination of specific differences between countries reveals that the weakening of the information environment for connected firms is prevalent in countries that have high levels of corruption, no electoral democracy, and low media penetration. Further analysis shows that this degradation is significant only if the firm is connected to the highest echelons of the country's leadership and the connected party in the firm is the controlling shareholder. In conjunction with earlier literature, our findings suggest that political rent-seeking weakens both the public and the private information environments for connected firms in emerging economies with weak political processes and low media penetration.